The optimization of cellulose nanofibre (CNF) production from empty fruit bunch (EFB) using steam explosion pre-treatment - Muhammad Arif Fahmi, Supian (2019)
Empty fruit bunch (EFB) is 24% from the 168 million tonnes of lignocellulosic oil palm biomass generated in Malaysia that has a high cellulose content (up to 65%). Cellulose can be extracted by using thermochemical treatment and pre-treatment processes such as steam explosion that improve the efficiency of further thermochemical treatment process. Grinding is the most effective mechanical treatment to defibrillate the cellulose into cellulose nanofibre (CNF) and optimization of the grinding process can help to reduce the time and energy consumption of the process. The purpose of this study is to extract cellulose from EFB via steam explosion pre-treatment followed by thermochemical treatment and the optimization of mechanical treatment using response surface methodology (RSM) for CNF production. The extraction of cellulose starts with steam explosion pre-treatment at 20 bar at different retention time (3-10 min); hot water treatment at different period of time (15-90 min); alkaline treatment using sodium hydroxide (NaOH) at different concentration (2.5-20%); and bleaching using two different reagents (sodium hypochlorite and sodium chlorite) with different bleaching techniques (system 1 and 2). The optimization of CNF production start with screening of factors (speed, time and consistency) using the full factorial design (FFD) and central composite design (CCD) to generate the RSM for the identification of the optimum condition. Throughout the extraction of cellulose and production of CNF, the chemical properties, thermal characteristic and crystallinity of the treated fibre were analyzed using Fourier transform infrared spectroscopy (FTIR) thermogravimetric analysis (TGA) and x-ray diffraction (XRD); field emission scanning electron microscopy (FESEM) to observe the morphology and size of the steam exploded fibre, cellulose, and CNF. The chemical composition and properties of the extracted cellulose were analyzed using a standard method such as TAPPI method. FESEM shows that the steam explosion at 10 min helped to rupture the structure of the EFB fibre. FTIR and TGA showed that the chemical properties and thermal characteristic of the fibre were not affected throughout the extraction of cellulose and production of CNF. XRD showed that the crystallinity of the fibre increased as the number of treatments increased but the crystal domain size of the fibre had fluctuated as the fibre undergoes all the treatments for cellulose extraction. TAPPI indicated that the extracted cellulose was 85.2% (wt), a high cellulose content, and almost all lignin has been removed, leaving only 0.07% (wt) of it. FFD had helped to screen out the consistency of fibre as it gave the least contribution during the mechanical treatment and the RSM showed that the best condition for CNF production is at 722 rpm, 30 min, and 5% consistency. FESEM shows that the mechanical treatment has decreased the size of cellulose from 8.25 μm to 17.85 nm for CNF. In conclusion, cellulose was successfully isolated from the EFB and the production of CNF is optimized which had greatly reduced the energy consumption of the mechanical treatment. This is great for the industrial application and is environmentally friendly.